(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Al-Hadeithi ZSM, Jasim SA, Salahdin OD. 2022. Relation between resistance of Klebsiella pneumoniae to certain antibiotics and ESBL/PBP genes. Biodiversitas 23: 3902-3906. One of the most effective antibiotics on microbes or in treating infections caused by these most resistant microbes, as it belongs to the beta-lactam group such as cephalosporin and carbapenems, which are considered among the most important antibiotics that have wide activity compared to the rest of the other antibiotics and their effectiveness against two types of negative and positive bacteria. Antibiotic resistance is a major public health concern because it happens when antibiotics are used too much or not in the right way. The improved resistance of Klebsiella pneumoniae against the antibiotics because of the virulence factors make K. pneumoniae is the most prevalent pathogenic bacteria behind nosocomial infections. Finding demonstrates that ?-lactamase is implicated in K. pneumoniae antimicrobial resistance to ?-lactam antibiotics. The purpose of this study was to look into the relation among Extended-spectrum beta-lactamase (ESBL), and the molecular biological mechanisms of antibiotic resistance in K. pneumoniae. Through the period from February to July 2021 a total of 100 out of 350 isolates were found to be K. pneumoniae. Cultural, morphological, and biochemical studies were used to identify growth on blood agar and MacConkey agar. The results revealed that the tested isolates were highly resistant to Imipenem (63%) and Amikacin (24%), while Amoxi-clav exhibited poor resistance (2%). The qualitative real-time approach was used to detect BlaR1 and Bla1 genes for positive isolates that’s possess gene/ resistant isolate , and the findings revealed that 2 (16%), 4 (33%), 16 (88%), 7 (38%), 24 (100%), 20 (83%), 2 (66%), 2 (100%), 2 (100%), 60 (95%), and 57 (90%) for CIP, CRO, AK, TMP, AMC, and IMP respectively.